Liveworksheet: E-LKPD Based On Project-Based Learning On Science And Science Learning To Improve Critical Thinking Skills - Resyi Abdul Gani; Windiyani, Tustiyana; Liah, Rina; Chika Heryanti, Aldila (PT. Banjarese Pacific Indonesia, 2025)
The purpose of this research is to develop E-LKPD based on project-based learning assisted by live worksheet science learning to improve understanding of concepts in elementary schools and the effectiveness of E-LKPD based on project-based learning assisted by live worksheet, as well as to find out the response of teachers and students in grade V of SDN Dewi Sartika 2 Aut The implementation of E-LKPD single substance material plays a role in improving thinking skills through classroom learning. The type of research is the ADDIE model approach, (Analysis, Design, Development, Implementation, and Evaluation). The product validation test was conducted by computer science media experts, Indonesian language experts, and science material experts. The validation results by media experts were 89.0% of the criteria were very feasible, linguists 96.0% of the requirements were very doable, and science materials experts 90.3% were very feasible. The results of the student response questionnaire were 91.5%, the response of class teachers was 90% in the appropriate category, and the average effectiveness score of using E-LKPD was 89.6% of the criteria as expected. The results show that project-based learning E-LKPD using live worksheets is feasible to use in the learning process and is effective in improving the thinking skills of elementary school students.